Molluscum contagiosum in human immunodeficiency virus infected patients - Chaudhary Mayur; Kulkarni Meena (Wolters Kluwer Medknow Publications, 2008)
Molluscum contagiosum (MC) is a cutaneous lesion caused by a DNA virus from the poxvirus family. Worldwide in distribution, MC is most frequently encountered as an easily treated disease of childhood and has rarely been a cause of serious morbidity. With the advent of new populations of immunocompromised individuals, especially those infected with the human immunodeficiency virus (HIV), MC has emerged as a difficult clinical challenge and the focus of renewed interest for dental professionals. This article presents four cases of HIV positive patients afflicted by MC along with a review of the literature on this dermatopathological lesion.